Investigation of the efficacy of tyrosol on doxorubicin-induced acute cardiotoxicity in rats - Mustafa Cellat; Muhammed Etyemez (Eurasian Journal of Veterinary Sciences)
Aim: In this study, it was aimed to investigate the efficacy of tyrosol on cardiotoxicity induced by doxorubicin. Materials and Methods: Rats were divided into 4 groups and each group included 8 rats. Groups 1 and 2 were given 1 ml of physiological saline, while groups 3 and 4 were given 20 mg/kg of tyrosol. In saline and tyrosol administrations, the oral gavage method was used. In addition, a single dose of 15 mg/kg dose of doxorubicin was administered intraperitoneally to group 2 and group 4 on the 12th day of the trial. On the 14th day of the experiment, serum and tissue samples were taken from the anesthetized rats and then euthanized. Serum creatine kinase MB and creatine kinase activities were analyzed. Heart tissues were extracted, and histological and oxidative stress characteristics were measured in these tissues. Heart tissue malondialdehyde and reduced glutathione levels, catalase and glutathione peroxidase activities were assessed spectrophotometrically. Results: Tyrosol pretreatment inhibited doxorubicin-induced increase in heart tissue malondialdehyde level (p<0.05), the decrease in reduced glutathione level and glutathione peroxidase enzyme activity, and suppressed doxorubicin-induced oxidative stress in the heart tissue. In terms of cardiac tissue catalase enzyme activity, no differences were found between the groups. Because of the reduction in oxidative damage in the heart, the serum creatine kinase MB and creatine kinase activity decreased dramatically (p<0.05). Furthermore, it was discovered that tyrosol pretreatment reduced the histopathological lesions caused by doxorubicin in cardiac tissue. Conclusion: It is thought that the administration of tyrosol may reduce the cardiotoxicity caused by doxorubicin.